Modern Directions of Advanced Training of Teachers in Preschool Educational Institutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the modern directions of advanced training for teachers in preschool educational institutions, with a focus on current professional development (PD) practices and the gaps within existing training programs. The knowledge gap identified in this research revolves around the insufficient integration of digital literacy and inclusive education training for preschool teachers in Uzbekistan. The study utilizes a qualitative, survey-based methodology to gather data from 30–40 preschool teachers who have participated in advanced training programs. Findings indicate that while modular and flexible CPD systems, digital tools, and inclusive education strategies have contributed to improved teaching practices, significant barriers remain, particularly in rural areas where access to digital platforms is limited. Teacher confidence in using digital tools and specialized training in inclusive education are key areas in need of improvement. The study suggests that systemic, scalable CPD models and region-specific training initiatives can address the existing gaps and ensure equitable access to PD across urban and rural settings. The study's implications highlight the need for policy interventions that promote the institutionalization of CPD programs, and further research is recommended to explore the long-term impact of digital and inclusive education training on teacher effectiveness and child development outcomes.